Charge transfer and ultrafast nuclear motions: the complex structural dynamics of an electronically excited triamine. Issue 1 (26th October 2015) - Cheng, Xinxin; Gao, Yan; Rudakov, Fedor; Weber, Peter M.
Abstract : Time-resolved Rydberg fingerprint spectroscopy combined with quantum chemical calculations reveals the complex structural dynamics and charge transfer in real time. Abstract : Three ionization centers make 1, 3, 5-trimethyl-1, 3, 5-triazacyclohexane (TMTAC) an interesting model system to study intramolecular charge transfer (CT). Because the molecule assumes a C s symmetric, axial–equatorial–equatorial (aee) conformation in the ground state, there are two distinct types of the nitrogen atoms. We discovered that either nitrogen atom can be ionized independently so that two molecular cations exist with different (localized) charge distributions in the Franck–Condon region. The initially localized charge can delocalize via CT, provided the molecule acquires a suitable structural geometry. These proper structures are all found to have a common structural motif that supports CT via through-space-interaction. The structural dynamics and the CT process in Rydberg-excited TMTAC, where the molecular ion core closely resembles the ion, were probed by time-resolved Rydberg fingerprint spectroscopy. When TMTAC is excited at 230 nm to the Franck–Condon region of the 3s Rydberg state, the two types of nitrogen atom Rydberg chromophores give rise to distinct binding energy peaks. The sequential molecular responses that follow the Rydberg excitation manifest themselves as time-dependent changes of the binding energy and are observed by ionization at 404 nm. A fast transition with 103 fs time constant was attributed to a motion that leads to a local minimum of the charge-localized state on the Rydberg potential energy surface. Because a large amount of energy is deposited into the vibrational manifolds, the molecule continues to sample the potential energy surface and eventually reaches a dynamic equilibrium between charge-localized and charge-delocalized states. The forward and backward time constants were determined to be 1.02 ps and 4.09 ps, respectively. The binding energy spectrum also reveals the existence of an equilibrium among several charge-delocalized states. Quantum chemical calculations were carried out to find the stable minima of the ground state and the ion state. The binding energies of the Franck–Condon structures and the relaxed ion structures were calculated using the Perdew–Zunger self-interaction corrected DFT (PZ-SIC) method to assign the spectra at time zero and at equilibrium, respectively.